Indigenous schools. Intercultural contexts, perceptions and challenges - Adecir POZZER; Elcio CECCHETTI (Ediciones Universidad de Salamanca, 2020)
The article deals with the indigenous school in Brazil, its principles, objectives, organization and contemporary challenges. Reflect critically on aspects related to the conditions and possibilities of cultural and technical training of indigenous students, as well as the epistemic-methodological dimension that underpins intercultural indigenous school education. It is a qualitative reflection, whose adopted methodology is bibliographic and documentary. By analyzing the few advances that have been made in recent decades and the many challenges that remain, it can be concluded that indigenous school education lacks greater autonomy and state investment, so that indigenous communities themselves can gradually manage their school units. Even in the face of numerous difficulties, the experiences of intercultural indigenous school education have provided greater recognition, appreciation and respect for thought, life forms and sciences produced within indigenous communities, even though they are on the margins of hegemonic cultural, economic and political systems.